(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2011)
New and rediscovered records of three species of orchids (Anacamptis palustris, Dactylorhiza incarnata and Goodyera repens) are provided from the Chernigiv Polissya in the Desna River valley between Kyiv and Chernigiv.